The sound design of the Twin Peaks series and Alain Splet’s heritage (RuMoRes, 2019)
This article examines the sound design of the television series Twin Peaks, created by David Lynch and Mark Frost. The focus is on the distortions or substitutions of voices, which are techniques that Lynch had used in a short and four feature-length films, with the sound designer Alan Splet. The aim is to identify any remains of Splet’s type of sound creation in the series, produced after the end of his partnership with Lynch. The analysis of the latest Twin Peaks season (2017) shows sound resources of earlier seasons have been intensified, in conjunction with the more daring plot concerning its storytelling. This article is based on Michel Chion regarding sound and on Luiz Manzano regarding sound design. James Carse’s concept of infinite game and Angela Hague’s essay on the agent Cooper’s investigative method help in understanding the relation between sound and fictional plot.